Respuesta :
[tex]|AB|=\sqrt{(x_B-x_A)^2+(y_B-y_A)^2}[/tex]
A(-6;4), B(3,4)
[tex]|AB|=\sqrt{(3+6)^2+(4-4)^2}=\sqrt{9^2+0^2}=\sqrt{9^2}=\sqrt{81}=9[/tex]
A. |-6|+|3|=6+3=9 True
B. |3|-|-6|=3-6=-3 False
C. |-6|+|-4|=6+4=10 False
D. |4|-|-6|=4-6=-2 False
The answer: A
:)
A(-6;4), B(3,4)
[tex]|AB|=\sqrt{(3+6)^2+(4-4)^2}=\sqrt{9^2+0^2}=\sqrt{9^2}=\sqrt{81}=9[/tex]
A. |-6|+|3|=6+3=9 True
B. |3|-|-6|=3-6=-3 False
C. |-6|+|-4|=6+4=10 False
D. |4|-|-6|=4-6=-2 False
The answer: A
:)
Answer:The answer is C
A) (3, 6)
B) (6, 3)
C) (−3, 6)
D) (−3, −6)
Step-by-step explanation:
Point A' represents the reflection of point A across the x-axis. Which coordinate pair represents the location of point A before the transformation?